The effects of the computer assisted language learning on vocabulary acquisition on the level two students of SK Sg. Maong Hilir, Kuching / Julia Baki - Baki, Julia (2004)
This study investigated the effects of computer-assisted language learning on vocabulary acquisition on the students of S K Sg. Maong Hilir, Kuching. Thirty subjects were randomly assigned to two groups and each group was randomly assigned to one of the two treatments. The experimental group was taught using the multimedia annotation. There were twenty low frequency words. The words were the names of buildings and places. The words were annotated with text, sound and pictures. The control group was taught using the traditional method that is chalk and talk. The teacher explained the words and drew the pictures on the blackboard. The students were encouraged to jot down notes and draw the pictures of buildings and places to enhance the long term retention. The subjects were given a pre test before the lesson to check whether they were familiar with the words. After the lesson, an immediately post test was administered to see the effects of the computer assisted language learning. Two weeks later, another test was given. This was to determine the long term retention. The study produced evidence that students learnt vocabulary better when they watch the pictures and listen to the definition of the words with text. In addition, annotations containing text, sound and pictures were found to be more helpful for vocabulary learning than the traditional method. However, in order to obtain a more reliable and generalizable result, a replication study with a bigger number of subjects is needed.